2012
DOI: 10.1007/s10591-012-9186-6
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Medical Family Therapy Through Research: A Consideration of Qualitative, Quantitative, and Mixed-Methods Designs

Abstract: To survive in today's healthcare climate, stakeholders across all mental health disciplines must work to produce empirical evidence that earns their fields' regard by educators, providers, and policy makers. As the field of Medical Family Therapy (MedFT) answers this call, it will be important for researchers to clearly define, characterize, and assess MedFT practice across clinical, operational, and financial arenas of care. In this account, we propose a common lexicon from which to do this, highlighting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As its practice is better articulated (McDaniel et al, 2014) and its applications are better described (Hodgson et al, 2014), it is expected that the research base will improve. Field leaders are aggressively advancing calls to extend investigative efforts across primary, secondary, and tertiary care environments, and to honor clinical, operational, and financial facets of care along the way (Hodgson et al, 2014;Mendenhall, Pratt, Phelps, & Baird, 2012;Mendenhall, Pratt, Phelps, Baird, & Younkin, 2014).…”
Section: Assessing the Evidence: Next Steps In Medical Family Therapy...mentioning
confidence: 99%
“…As its practice is better articulated (McDaniel et al, 2014) and its applications are better described (Hodgson et al, 2014), it is expected that the research base will improve. Field leaders are aggressively advancing calls to extend investigative efforts across primary, secondary, and tertiary care environments, and to honor clinical, operational, and financial facets of care along the way (Hodgson et al, 2014;Mendenhall, Pratt, Phelps, & Baird, 2012;Mendenhall, Pratt, Phelps, Baird, & Younkin, 2014).…”
Section: Assessing the Evidence: Next Steps In Medical Family Therapy...mentioning
confidence: 99%
“…Family-centered, collaborative, biopsychosocial models of health care have also grown and evolved (Doherty & Baird, 1983; Engel, 1977; Kissane & Parnes, 2014; McDaniel, Doherty, & Hepworth, 2014; Miller, McDaniel, Rolland, & Feetham, 2006; Peek, 2015; Rolland, 1994, in press; Seaburn, Gunn, Mauksch, Gawinski, & Lorenz, 1996; Talen & Valeras, 2013; Wood et al, 2008; Wright & Bell, 2009). There is substantial evidence for the mutual influence of family functioning, health, and physical illness (Carr & Springer, 2010; D’Onofrio & Lahey, 2010; Proulx & Snyder, 2009; Weihs, Fisher, & Baird, 2002) and the usefulness of family centered interventions with chronic health conditions (Campbell, 2003; Hartmann, Bazner, Wild, Eisler, & Herzog, 2010; Kazak, 2006; Law, Crane, & Berge, 2003; Martire, Lustig, Schulz, Miller, & Helgeson, 2004; Martire, Schulz, Helgeson, Small, & Saghafi, 2010; Mendenhall, Pratt, Phelps, & Baird, 2012; Shields, Finley, Chawla, & Meadors, 2012). These systematic reviews summarize the increasing body of research regarding the impact of serious illness on families across the life span and the relationship of family processes to illness behavior, adherence, and disease course.…”
Section: Family Systems In Health Carementioning
confidence: 99%
“…For example, it has been suggested that utilizing different titles such as "Clinical Specialists" that focus on HSW competency in clinical practice could emphasize such contributions . Finally, emerging practice-based research that highlights the importance of social work to positively impact patient outcomes and experiences (Luzinski 2012;Mendenhall, Pratt, Phelps, & Baird, 2012;Peek, 2008) should be pursued.…”
Section: Implications For Research and Practicementioning
confidence: 99%